2021
DOI: 10.1101/2021.06.16.21258817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mass mask-wearing notably reduces COVID-19 transmission

Abstract: Mask-wearing has been a controversial measure to control the COVID-19 pandemic. While masks are known to substantially reduce disease transmission in healthcare settings (Howard et al 2021), studies in community settings report inconsistent results (Brainard et al 2020). Investigating the inconsistency within epidemiological studies, we find that a commonly used proxy, government mask mandates, does not correlate with large increases in mask-wearing in our window of analysis. We thus analyse the effect of mas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Since late August 2021, mask wearing in England has decreased by approximately 30% 33 . We assume that this decrease could be completely reversed by the face covering measure, and that this would result in a 7.5% reduction in R over the contingency period, comparable to the effect size measured in a regression analysis across 92 regions 34 and a cluster randomized trial in Bangladesh 35 .…”
Section: Vaccination Waning and Intervention Scenariosmentioning
confidence: 84%
“…Since late August 2021, mask wearing in England has decreased by approximately 30% 33 . We assume that this decrease could be completely reversed by the face covering measure, and that this would result in a 7.5% reduction in R over the contingency period, comparable to the effect size measured in a regression analysis across 92 regions 34 and a cluster randomized trial in Bangladesh 35 .…”
Section: Vaccination Waning and Intervention Scenariosmentioning
confidence: 84%
“…With each survey version, new questions have been added in conjunction with epidemiologists, local government input, and research partners. Other studies have used these data to investigate a range of insights, including masking effectiveness, testing practices, and vaccine hesitancy, and there is potential to further understand knowledge, attitudes, and practices through this high-density data stream (30,(47)(48)(49)(50). Indeed, the survey has most recently incorporated items to survey social impacts, vaccine uptake, and vaccine hesitancy (31).…”
Section: Discussionmentioning
confidence: 99%
“…3 Non-randomized studies have also generally found that high levels of compliance are needed to reduce transmission at the community level. [28][29][30] Thus, effectiveness facemask mandates to reduce population-level transmission of COVID-19 requires both high levels of mask-wearing -and importantly the ability accurately measure actual compliance. Commonly used self-reported surveys are likely overestimating facemask compliance.…”
Section: Discussionmentioning
confidence: 99%